Supplements and adjustments to the method of the assessment of the effective dose from the external exposure of the patients - V. Yu. Golikov; L. A. Chipiga; A. V. Vodovatov; S. S. Sarycheva (Радиационная гигиена)
The current study was aimed at the justification and proposal of the supplements and corrections that are planned for the implementation in the updated version of the Methodical guidelines “Control of the effective doses of the patients from the X-ray examinations” (MU 2.6.1.2944-11). This study included estimation and/ or update of the values of the conversion coefficients from measurable dose characteristics (entrance-surface dose, dose-area product) to the effective dose for various X-ray examinations. Estimation of the updated conversion coefficients was based both on the home analytical and experimental studies based on the modern protocols of the X-ray examinations, and the results of the published data. Updated values of the conversion coefficients were presented for: fluoroscopic examinations of the gastro-intestinal tract with barium media for adult and pediatric patients; interventional examinations of the adult patients; computed tomography examinations for adult and pediatric patients; dental intraoral examinations. For the first time, the methods of the estimation of the effective dose and corresponding conversion coefficients were presented for: computed tomography of the extremities, whole body, scan of several anatomic regions; angiographic examinations of the heart vessels of the pediatric patients of different age categories; slot-scanning X-ray examinations; bone densitometry.